FATE OF VACLOVAS BIRŽIŠKA’S ALEKSANDRYNAS AND OTHER MANUSCRIPTS AFTER THE END OF THE SECOND WORLD WAR - LIEPAITĖ, INGA; ŠULGIENĖ, NIJOLĖ (Knygotyra, 2012)
The article deals with the relations between Prof. V. Biržiška and his former student P. Lukošiūnas. It is based on archival and published sources and, with regard to provided options, tries to disclose the fate of Professor’s manuscripts prior to and after his retreat from Lithuania to the West in the summer of 1944. The conclusion was made that V. Biržiška had brought away part of his manuscripts piled up in trunks. Actually, the manuscript of Aleksandrynas had to be among those manuscripts, although V. Biržiška assumed that it could have been not complete. The complicated fate of the survival of the latter manuscript is confirmed by the content of the letter of P. Lukošiūnas to V. Biržiška, provided in the annex to the article. Before his departure from Lithuania, V. Biržiška had entrusted part of his manuscripts to his former nurse O. Butkaitė who was still living in Viekšniai in his parents’ house, and to his other close friends, among them, for example, to V. Steponaitis. As shown by the accumulated memoir literature, the fate was unsparing to the manuscripts that were safeguarded by the nurse: several times they avoided the fires of the war, but their end was still marked by fire: they were burnt by the nurse herself before her death. Part of his manuscripts V. Biržiška had secured as far back as in 1941, and on the basis of these documents later, in the then Library of the Lithuanian Academy of Sciences, the formation of a separate collection was started. Part of Professor’s manuscript heritage appeared in other libraries due to the efforts of J. Rimantas and K. Korsakas.
Keywords: ...